Fc epsilon RI-mediated tyrosine phosphorylation and activation of the 72-kDa protein-tyrosine kinase, PTK72, in RBL-2H3 rat tumor mast cells. - Hutchcroft, J E (1992)
In RBL-2H3 rat tumor mast cells, cross-linking the high-affinity IgE receptor Fc epsilon RI causes tyrosine phosphorylation of multiple proteins. These phosphoproteins include phospholipase C gamma 1, the beta and gamma subunits of the Fc epsilon RI, the Src family protein-tyrosine kinase Lyn, and a 72-kDa protein that coimmunoprecipitates from lysates of antigen-stimulated cells with antibody to the receptor beta subunit. We now present evidence that the 72-kDa Fc epsilon RI-associated protein is the protein-tyrosine kinase PTK72 that forms part of the antigen receptor complex in B lymphocytes. The identification is based on immunoreactivity with anti-PTK72 antiserum, chromatographic profiles on the affinity resin heparin/agarose, and one-dimensional phosphopeptide mapping studies. Enzymatic activity of the kinase is increased in anti-PTK72 immune complexes prepared from lysates of antigen-activated RBL-2H3 cells. The 72-kDa protein-tyrosine kinase is the principal substrate for in vitro tyrosine phosphorylation in anti-phosphotyrosine immunoprecipitates of RBL-2H3 cells. The discovery that RBL-2H3 mast cells share a receptor-activated protein-tyrosine kinase, PTK72, with B lymphocytes provides additional support for the existence of common signaling pathways initiated by multichain immune recognition receptors.